2012
DOI: 10.1007/s10346-012-0322-z
|View full text |Cite
|
Sign up to set email alerts
|

Locating, monitoring, and characterizing typhoon-linduced landslides with real-time seismic signals

Abstract: Landslides induced by typhoon Morakot during its passage across Taiwan on 7-9 Aug 2009 claimed more than 700 lives and caused heavy economic loss. Unlike earthquake monitoring, precise locations of landslides could not be determined in nearreal time because their seismic phases are difficult to identify. Here, we show that large, damaging landslide events are characterized seismically by a distinct waveform pattern of frequent intermixes of P and S waves over a time window of several tens of seconds. The predo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 17 publications
0
27
0
Order By: Relevance
“…In their studies, Surinach et al (2005) and Dammeier et al (2011) reported that rockfall spectrograms show a typical triangular shape that could be related to source effects, material entrainment during propagation and/or progressive failure and individual block impacts (Norris, 1994;McSaveney and Downes, 2002). All these characteristics can be used for event detection at different scales (Helmstetter and Garambois, 2010;Yamada et al, 2012;Kao et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In their studies, Surinach et al (2005) and Dammeier et al (2011) reported that rockfall spectrograms show a typical triangular shape that could be related to source effects, material entrainment during propagation and/or progressive failure and individual block impacts (Norris, 1994;McSaveney and Downes, 2002). All these characteristics can be used for event detection at different scales (Helmstetter and Garambois, 2010;Yamada et al, 2012;Kao et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…However, it should be kept in mind that larger mass wasting events can have a distinct long‐period signal, 10–30 s, that may be recorded at great distance [ Lin et al ., ; Ekström and Stark , ]. Smaller landslides produce seismic signals that last several minutes, sometimes up to tens of minutes, with high amplitudes, irregular envelopes, and a lack of distinctive arrivals of P and S seismic phases [ La Rocca et al ., ; Suriñach et al ., ; Favreau et al ., ; Kao et al ., ]. The seismic energy is dominant in the 0.1–10 Hz frequency band but long‐period waves can be recorded [ Favreau et al ., ].…”
Section: Seismological Methodsmentioning
confidence: 99%
“…We then applied a 1 s smoothing window to the amplitude functions. This corresponds to the weighting factor W m in Kao et al [2012], fixed at a value of 1. For a set of smoothed amplitude functions, we then calculated the signal to noise ratio (SNR) in order to determine the quality of the seismic data before migration.…”
Section: Amplitude Functionmentioning
confidence: 99%
“…The SSA was originally designed to locate non‐volcanic tremors with emergent arrivals (Kao & Shan 2004). Recent development of the SSA has expanded its application to other seismological problems such as the rapid identification of fault planes for earthquakes (Kao & Shan 2007; Kao et al 2008), delineation of source characteristics of earthquake doublets (Kan et al 2010) and near‐real‐time epicentral determination of landslides (Kao et al 2012).…”
Section: Methodsmentioning
confidence: 99%